The Company's Working Capital during the Covid-19 Pandemic to Increase the Profitability Limited Company Telkomsel in Makassar City - Muhammad Luthfi Siraj; Aslinda Aslinda; M Awaluddin; Maya Kasmita; Andi Caesar To Taddampali (Universitas Negeri Makassar, 2020)
This study aims to determine the optimization of working capital in increasing the profitability of Limited Company Telkomsel. The research method used is descriptive with a quantitative approach using financial statement data sources for the three years 2017 to 2019. This research uses observation data collection techniques, questionnaires and documentation. Descriptive analysis method and inferential statistical analysis with financial ratio analysis by comparing the current ratio with the ratio in the previous year. From the analysis and discussion results indicate that Limited Company Telkomsel, experienced that the overall working capital management was not optimal from 2017 to 2019. Working capital management could not run optimally because of the working capital turnover that occurred at Limited Company Telkomsel only reached the highest number of 4.42 times, while looking at the lowest cash turnover in 2019 which reached 2.61 times. Turnover of working capital at Limited Company. Although it is considered that Telkomsel has a fairly optimal cash and receivable turnover rate, this has not been able to significantly increase the company's profitability compared to previous years.